The impact of culture on the management of subsidiary organizations: the case of Viettel in Peru - Rees, Gareth H. (2020)
As south-south investments increase so do the issues experienced by investing companies. One of these is the impact of culture. This article analyzes the effects of the subsidiary country culture on an investing firm’s organizational culture and the managerial practices used to address them. Data is gathered from cultural databases, a company-wide survey and semi structured interviews. Descriptive statistics are used to reveal country and organizational culture differences, with content analysis to expose management responses. There is a clear difference between the firm’s Vietnamese and Peruvian workers, with the company’s practices more amenable to the Vietnamese employees. Recognition of this has resulted in a number of initiatives to reduce its impact. The study’s results offer suggestions that may be valued by other foreign companies interested in operating in Peru and may be especially relevant to Southeast Asia and Asian companies interested in investing in or looking to start operations in Latin America.